A measurement setup for acquiring the local magnetic properties of plastically deformed soft magnetic materials - Bi, Shasha; Sutor, Alexander; Lerch, Reinhard; Xiao, Yunshi (Journal of Applied Physics, 2011)
This paper introduces a new measurement setup for extraction of the local magnetic properties. With the help of finite element method simulations, modifications are made on the previous double-C-yoke method. Small dimension measuring coils are applied in the stray field produced by the magnetic circuit to evaluate the local magnetic properties of the specified part of the specimen. Through the measurements with the plastically deformed materials at different temperatures, it indicates that the magnetic properties of soft magnetic materials are quite sensitive to plastic straining. After high-temperature thermal treatment on the plastically deformed specimen, the local magnetic properties exhibit an obvious recovery. (C) 2011 American Institute of Physics. [doi:10.1063/1.3535549]

A modified Preisach hysteresis operator for the modeling of temperature dependent magnetic material behavior - Sutor, Alexander; Rupitsch, Stefan; Bi, Shasha; Lerch, Reinhard (Journal of Applied Physics, 2011)
In this paper, we present a model for temperature dependent hysteretic nonlinearities with nonlocal memories. This model can be applied to describe hysteretic material behavior. Common applications are ferromagnetic or magnetostrictive materials. Our model consists mainly of a Preisach operator with a continuous Preisach weight function. We choose a weight function which shows a strong correlation between the function's parameters and certain properties of the hysteresis curve. As a new approach, the weight function is written as a function of temperature. The model parameters are customized to a set of symmetric hysteresis curves. We verify our model for magnetic materials with differently shaped hysteresis curves, different temperatures and magnetic field amplitudes. (C) 2011 American Institute of Physics. [doi:10.1063/1.3562520]

An efficient inverted hysteresis model with modified switch operator and differentiable weight function - Bi, Shasha; Sutor, Alexander; Lerch, Reinhard (Proceedings of IEEE Magnetics Summer School, 2013)

An Efficient Inverted Hysteresis Model with Modified Switch Operator and Differentiable Weight Function - Bi, Shasha; Sutor, Alexander; Lerch, Reinhard; Xiao, Yunshi (IEEE Transactions on Magnetics, 2013)
This paper proposes a different inverted hysteresis model with modification of the classic Preisach switch operator. By using this new switch operator, the inverted model remains the wiping out and congruency properties. It also guarantees the symmetry and total positiveness of weight function in the Preisach plane. According to the change pattern of H(B) branches, a differentiable weight function is introduced in the inverted model. The weight function performs with good continuity and symmetry. This makes it possible to implement the inverted model in numerical analysis without iterative procedure. The identification work is done by means of the measured major loops. Here the Newton method algorithm is applied to optimize the mean squared error (MSE) between the measured and simulated data. By this way, the limited number of parameters can be determined. The inverted model was verified for both soft and hard magnetic materials. Besides major hysteresis loops, minor loops and first-order reversal curves (FORCs) can also be simulated. By comparison, the simulation results produced by the inverted hysteresis model show good approximation to the measurement data.
Keywords: Differentiable weight function; finite element method; inverted hysteresis model; switch operator

An Inverted Preisach Model with Analytical Weight Function and its Numerical Discrete Formulation - Bi, Shasha; Wolf, Felix; Lerch, Reinhard; Sutor, Alexander (Proceedings of INTERMAG2014, 2014)

An Inverted Preisach Model With Analytical Weight Function and Its Numerical Discrete Formulation - Bi, Shasha; Wolf, Felix; Lerch, Reinhard; Sutor, Alexander (IEEE Transactions on Magnetics, 2014)
This paper proposes a numerical discrete formulation for an inverted hysteresis model, which is based on the classic Preisach model, but applies an inverted switch operator. The inverted switch operator is modified from the switch operator of the classic Preisach model. By applying this inverted switch operator, the inverted model retains the wiping-out and congruency properties. The distribution of the weight function can be approximated with an analytical function. By means of a quasi-Newton method algorithm, the small number of parameters in this function can be directly determined from major loops. Iterative procedure is circumvented in the implementation of this model in finite-element analysis. The simulated hysteresis loops, such as minor loops and reversal curves, show good agreement to the measurement data. To realize efficient numerical calculation, the integral expression of the inverted model is rewritten in a discrete form. The double integration of the weight function is numerically approximated in the precalculation stage. In this way, it costs low memory usage and short calculation time during the calculation procedure.
Keywords: Analytical weight function; finite-element (FE) method; inverted hysteresis model; numerical discrete formulation

Identification and Verification of a Preisach Based Vector Model for Ferromagnetic Materials - Sutor, Alexander; Bi, Shasha; Lerch, Reinhard (Proceedings of INTERMAG2014, 2014)

Identification and verification of a Preisach-based vector model for ferromagnetic materials - Sutor, Alexander; Bi, Shasha; Lerch, Reinhard (Applied Physics A-Materials Science & Processing, 2015)
In many applications of ferromagnetic materials concerning sensors and actuators, magnetic fields are rotating. In order to precisely describe the behavior of ferromagnetic materials in rotating magnetic fields, vector hysteresis models are necessary. Therefore, much effort is being put into the development of efficient vector models. For the reason of computational efficiency, models have been developed that differ from the Preisach approach and are for example based on rotationally coupled step functions. We have proposed a very efficient Preisach-based model before, which we called the rotational vector Preisach model. In this paper, we propose an extension of the rotational switching function, which improves the model characteristics for arbitrary H-field trajectories. We also introduce a set of special vectorial minor loops for the general validation and comparison of vector models. We apply those H-field trajectories to isotropic materials such as sputtered FeCo thin films as used in micromechanical systems. The vectorial minor loops can readily be utilized to evaluate the model output, and the results agree well with vectorial measurements.

Identification and Verification of a Vector Model for Ferroic Materials - Sutor, Alexander; Bi, Shasha; Lerch, Reinhard (ITG-Fachbericht Sensoren und Messsysteme 2014, 2014)

Validation of the rotational vector Preisach model with measurements and simulations of vectorial minor loops - Sutor, Alexander; Bi, Shasha; Lerch, Reinhard (Applied Physics A-Materials Science & Processing, 2013)
In order to precisely describe the behavior of ferromagnetic materials in rotating magnetic fields, vector hysteresis models are necessary. The extension of the Preisach model with vector methods is well known. Much research in this field is based on the Mayergoyz vector hysteresis model. The drawback of this kind of model is the computational effort for the additional integral in the vectorial Preisach operator. Therefore, much effort is being put into the development of efficient vector models. For the reason of computational efficiency, models have been developed that differ from the Preisach approach and are, for example, based on rotationally coupled step functions. We have proposed a very efficient Preisach based model before, which we called the rotational vector Preisach model. Here, we propose an extension of the rotational switching function of the mentioned model, which improves the model characteristics for arbitrary H-field trajectories. We also introduce a set of special vectorial minor loops for the general validation and comparison of vector models. We apply those H-field trajectories to isotropic materials like FeCo thin films as used in our micromechanical systems. The vectorial minor loops can readily be utilized to evaluate the model output and the results agree well with vectorial measurements.